(untitled) (Colombia Medica, 2009)
Goal: Terminal renal failure affects all the person’s life dimensions. The impact of this illness during adolescence is quite dramatic because the adolescent must live with the illness demands and the demands from this crucial developmental stage. Knowledge regarding the impact of the dialysis catheter on the adolescent’s life is spare. Methodology: A phenomenological study was carried out with 8 female and male adolescents that were in dialysis. Findings: The adolescents had to learn to live with the dialysis catheter in their body. The catheter became an obstacle to achieve their identity and deteriorated their physical appearance and peer relationships.